2021
DOI: 10.3390/microorganisms9102004
|View full text |Cite
|
Sign up to set email alerts
|

6S-Like scr3559 RNA Affects Development and Antibiotic Production in Streptomyces coelicolor

Abstract: Regulatory RNAs control a number of physiological processes in bacterial cells. Here we report on a 6S-like RNA transcript (scr3559) that affects both development and antibiotic production in Streptomyces coelicolor. Its expression is enhanced during the transition to stationary phase. Strains that over-expressed the scr3559 gene region exhibited a shortened exponential growth phase in comparison with a control strain; accelerated aerial mycelium formation and spore maturation; alongside an elevated production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…In Streptomyces coelicolor , positions of the previously published sRNAs are also included. The position of 6S-Like scr3559 was adopted from the 6S-Like scr3559 sequence reported in Figure 2B of Bobek et al (2021) . The position of ssrS /6S RNA was adopted from Mikulík et al (2014) , from the sequences of primers that were used to generate DNA template carrying T7 promoter for in vitro transcription of 6S RNA.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In Streptomyces coelicolor , positions of the previously published sRNAs are also included. The position of 6S-Like scr3559 was adopted from the 6S-Like scr3559 sequence reported in Figure 2B of Bobek et al (2021) . The position of ssrS /6S RNA was adopted from Mikulík et al (2014) , from the sequences of primers that were used to generate DNA template carrying T7 promoter for in vitro transcription of 6S RNA.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, ( Bobek et al, 2021 ) reported a new 6S RNA in S. coelicolor , which was named “6S-like scr3559 RNA.” It is expressed from the sco3558-sco3559 genomic locus but from the minus strand (the previously published 6S RNA sequence was expressed from the plus strand), with its transcription start site located at position 3,934,888 in the genome ( Bobek et al, 2021 ). This 6S-like RNA is processed and its 5′ end corresponds to position 3,934,820 ( Bobek et al, 2021 ). However, the processed 6S-like RNA was almost undetectable in wild type S. coelicolor by Northern blotting ( Bobek et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These are found in soils, manure, and other sources [ 18 , 19 ]. These are eubacteria and grow by forming filaments or mycelium and do not form the usual bacterial assembly as bacillary or coccoid forms [ 20 ]. They produce chained conidiospores from spore-bearing aerial hyphae.…”
Section: Introductionmentioning
confidence: 99%